2021
DOI: 10.3390/ijms222011199
|View full text |Cite
|
Sign up to set email alerts
|

Multiparameter Evaluation of the Platelet-Inhibitory Effects of Tyrosine Kinase Inhibitors Used for Cancer Treatment

Abstract: Current antiplatelet drugs for the treatment of arterial thrombosis often coincide with increased bleeding risk. Several tyrosine kinase inhibitors (TKIs) for cancer treatment inhibit platelet function, with minor reported bleeding symptoms. The aim of this study was to compare the antiplatelet properties of eight TKIs to explore their possible repurposing as antiplatelet drugs. Samples of whole blood, platelet-rich plasma (PRP), or isolated platelets from healthy donors were treated with TKI or the vehicle. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In a Btk-deficient murine model (Btk xid animals), platelet functions in response to GPIb-V-IX (GPIb) were reduced [17]. Recent attention shifted to platelet Btk as a potential therapeutic target in platelet-related thrombotic diseases [18][19][20][21][22][23], but clinically used Btk inhibitors affecting platelet functions may also cause bleeding events [22,24]. While the principal mechanism of Btk activation is well-defined in platelets (membrane recruitment combined with tyrosine phosphorylation of the critical sites Y223 and Y551) [1,25], there are still important open questions concerning Btk activation and steady-state regulation by other protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…In a Btk-deficient murine model (Btk xid animals), platelet functions in response to GPIb-V-IX (GPIb) were reduced [17]. Recent attention shifted to platelet Btk as a potential therapeutic target in platelet-related thrombotic diseases [18][19][20][21][22][23], but clinically used Btk inhibitors affecting platelet functions may also cause bleeding events [22,24]. While the principal mechanism of Btk activation is well-defined in platelets (membrane recruitment combined with tyrosine phosphorylation of the critical sites Y223 and Y551) [1,25], there are still important open questions concerning Btk activation and steady-state regulation by other protein kinases.…”
Section: Introductionmentioning
confidence: 99%
“…A potential limitation of this model is priming of platelets as they flow over one spot, therefore affecting responses to downstream spots, however control experiments demonstrated no differences in thrombus formation based on the order of coated proteins [ 37 ]. The flexibility of this model has resulted in its extensive use over the past few years in a diverse range of experiments including assessment of variations in thrombus formation between healthy individuals [ 39 ], assessment of coagulation under flow [ 41 , 42 ], phenotyping patients with platelet disorders [ 40 , 43 ▪ ], assessment of pharmacological GPVI and integrin α2β1 inhibitors [ 44 ], characterization of calcium entry pathways in platelets [ 45 ] and assessment of the platelet inhibitory effects of different cancer treatments [ 46 ].…”
Section: High-throughput In-vitro Modelsmentioning
confidence: 99%
“…However, those of specific relevance to patients with cancer undergoing surgical intervention relate to platelet function. Tyrosine kinase inhibitors are heterogeneous in terms of affinity for platelet TKs, and the mechanism by which TKIs disrupt platelet function is, therefore, varied [49]. Molecules including axitinib, sorafenib and sunitinib have been associated with reduced platelet count [50], and it has been demonstrated that sunitinib delays fibrin formation and inhibits thrombus formation [51].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%